Randomized controlled study comparing the hemodynamic response to laryngoscopy and endotracheal intubation with McCoy, Macintosh, and C-MAC laryngoscopes in adult patients - Faiza Sulaiman Buhari; Venkatesh Selvaraj (Wolters Kluwer Medknow Publications, 2016)
Background and Aims: Earlier studies have shown that the type of laryngoscope blade influences the degree of hemodynamic response to endotracheal intubation. The aim of the study was to evaluate the hemodynamic response to oral endotracheal intubation with C-MAC laryngoscopy and McCoy laryngoscopy compared to that of Macintosh laryngoscopy in adult patients under general anesthesia. Material and Methods: This is a prospective randomized parallel group study. Ninety American Society of Anesthesiologists I patients were randomly allotted into three groups. Group A - Macintosh laryngoscopy (control group). Group B - laryngoscopy with McCoy laryngoscope. Group C - laryngoscopy with C-MAC video laryngoscope. Heart rate (HR), systolic blood pressure (SBP), diastolic blood pressure (DBP), and mean arterial pressure (MAP) were monitored at baseline (just before induction), just before intubation (T0), 1 min (T1), 3 min (T3), 5 min (T5), and 10 min (T10) after intubation. Intergroup comparison of study parameters was done by unpaired sample t-test for normal data and Mann-Whitney U-test for skewed data. For within-group comparison, the repeated measures of ANOVA for normal data and Friedman followed by Wilcoxon signed rank test for skewed data were performed. Results: In C-MAC group, the HR was significantly higher than the Macintosh group at 3 min after intubation, whereas SBP, DBP, and MAP were significantly higher at 1 min. McCoy group showed a similar response compared to Macintosh group at all time intervals. Conclusion: C-MAC video laryngoscope has a comparatively greater hemodynamic response than Macintosh laryngoscope.